Suatu Kajian Tentang Lapangan Kabur dan Ruang Vektor Kabur - Muhammad Abdy; Syafruddin Side; Muhammad Edy Rizal (Jurusan Matematika FMIPA UNM, 2018)
This research redefine fuzzy fields and fuzzy linear spaces. Furthermore, we show some theorem that applies to both concepts of fields and linear spaces (classic and fuzzy concept).